Audiology and speech-language pathology practice in Saudi Arabia - Alanazi, Ahmad A. (International Journal of Health Sciences, 2017)
Objectives: Audiology and speech-language pathology (SLP) are relatively new professions in Saudi Arabia. The idea of establishing new audiology and SLP programs in some education facilities has become popular across Saudi Arabia; yet, four undergraduate and graduate programs are currently available. This study aimed to explore the fields of audiology and Speech-language pathologists (SLPs) in Saudi Arabia, obtain demography of audiologists and SLPs, understand their current practices, and identify their perspective on what both professions need to improve. Methods: A cross-sectional mixed methods study design was used to address the aim of this study. Two online surveys were prepared and distributed to reach a large number of audiologists and SLPs. Both surveys consisted of and close-and open-ended questions and primarily focused on three categories demography, audiology or SLP practices, and audiologists’ or SLPs’ perspective on their professions in Saudi Arabia. Results: A total of 23 audiologists and 37 SLPs completed the surveys (age range =21-50 years). The majority of respondents were from Riyadh with different academic qualifications and working experiences. Various practices were noticed among audiologists and SLPs who mainly worked in hospitals. Several suggestions regarding the development of audiology and SLP education and practice in Saudi Arabia are discussed. Conclusion: This study provides useful information about audiology and SLP education and practices in Saudi Arabia. Collaborative work between stakeholders to achieve high-quality educational and practical standards is critical. National database, clinical guidelines and policies should be developed, employed, and supervised. Further research is needed to improve education and practice of both professions in Saudi Arabia.